Erector spinae plane block and thoracic paravertebral block for breast surgery compared to IV-morphine: A randomized controlled trial - Gürkan, Yavuz; Aksu, Can; Kuş, Alparslan; Yörükoğlu, Ufuk H. (Journal of clinical anesthesia, 2020)
Erector spinae plane (ESP) block is a novel regional anesthesia technique and gaining importance for postoperative pain management. Since it was first described, the clinicians wonder if this new simple technique can replace paravertebral block (PVB). We aimed to compare the postoperative analgesic effect of ESP block and PVB with a control group in breast surgeries. Randomized controlled trial. Operating room. Seventy-five ASA I–II patients aged 25–65, who were scheduled to go under elective unilateral breast surgery for breast cancer were included to the study. Patients were randomized into three groups as ESP, PVB, and Control group. Ultrasound (US) guided ESP block and PVB with 20 ml 0.25% bupivacaine was done preoperatively to the patients according to their groups. All patients were provided with iv patient-controlled analgesia device for postoperative analgesia. Morphine consumptions and numeric rating scale (NRS) scores for pain were recorded at 1st, 6th, 12th and 24th hours postoperatively. There was a statistically significant difference between ESP and Control groups (p < 0,001) and between PVB and Control groups (p < 0,001), while there was no difference between ESP and PVB groups (p > 0,05) for 24-hour morphine consumptions. There was a significant difference between PVB and Control groups for NRS at postoperative 1st and 6th hour (p = 0.018 and p = 0.027 respectively). This study has shown that US guided ESP block and PVB provided adequate analgesia in patients undergoing breast surgery and have an opioid sparing effect by reducing morphine consumption. Clinical Trials Registry: NCT03480958. •ESP block provides effective analgesia in breast surgery.•ESP block has lower risk of complications compared to TPV block.•Both ESP block and TPV block have a similar analgesic effect in breast surgery.